Integrating the Xpert MTB/RIF Assay into a Diagnostic Workflow for Rapid Detection of Mycobacterium tuberculosis in a Low-Prevalence Area - Deggim, Vanessa (American Society for Microbiology, 2013)
The Xpert MTB/RIF assay is a rapid and fully automated real-time PCR assay. The performance of the Xpert MTB/RIF assay as a primary screening test for urgent clinical specimens was evaluated during a 2-year period. The results showed that replacing smear microscopy with the Xpert MTB/RIF assay facilitates laboratory handling and improves the sensitivity and specificity of Mycobacterium tuberculosis detection.